FOOD SECURITY CONDITIONS IN EAST PRIANGAN WEST JAVA: FOOD SAFETY OR FOOD INSECURITY? - Syahrul Ganda Sukmaya; Reny Hidayati; Atika Dyah Perwita; Lutfi Zulkifli (Universitas Garut, 2022)
Compared with the average poverty rate in the West Java Area, the poverty rate in the East Priangan Zone is very high. One measure of food insecurity is the high hunger rate in the country. The problem of food security has always been the biggest worry, as food is a fundamental human need, so economic growth is quite influential. The author is interested in researching the extent of food protection in the East Priangan Area on the basis of the significance and validity of the issues, as well as attempts to achieve food security. The study discusses different facets of food protection linked to farmers' households in the East Priangan Area. The report was undertaken in the East Priangan Area through a library study of numerous research findings and secondary evidence supporting food protection concerns. The issues explored are (1) the principle of food protection, (2) the efficiency of food security, and (3) the plan for realizing food security. The findings of the study showed that (1) the definition of food protection includes three foundations of food security, consisting of aspects of supply, access to food and utilization of food, (2) the degree of food security of districts and cities in eastern Priangan belongs to the very food safety group of food security, and (3) the techniques that can be applied to address the problems of food security.